"What Shall I Call You?" (with Julian of Norwich)1. Issue 2 (4th May 2019) - Joyce, Michael
ABSTRACT: Julian of Norwich (1342–1430), anchorite and seer, was, according to the twentieth-century mystic poet and monk Thomas Merton, "one of the most wonderful of all Christian voices" and "with Newman the greatest English theologian." Her Shewings, or Revelations of Divine Love, are an account, meditation, and teaching proceeding from sixteen visions she experienced on a single day in May of 1373. This "Soundproof Room" encounter takes the form of a mild creole of medieval and postmodern English of the sort that in prior works, most notably Paris Views and Foucault in Winter, in the Linnaeus Garden, the author has called "mixed language." Here also the author takes his cue from Merton's reputed avowal that "Rather than 'Sister', one calls her the 'Lady Julian', " by making dialogue a like instance of seeking how to address another.